A national survey of screening and management of hypogammaglobulinemia in Canadian transplantation centers. Issue 4 (24th May 2017) - Bourassa‐Blanchette, Samuel; Knoll, Greg; Tay, Jason; Bredeson, Christopher; Cameron, Donald W.; Cowan, Juthaporn
Abstract: Background: Infection remains one of the most common transplant‐related causes of death in patients undergoing transplantation. Secondary hypogammaglobulinemia (HGG) as a component of immune suppression and deficiency is associated with both solid organ transplantation (SOT) and hematopoietic cell transplantation (HCT). Available data and clinical experience for the supplementation of immunoglobulin (Ig) in these patients is conflicting, and differing clinical opinion accounts for non‐uniform practice in the use of Ig treatment. We aimed to survey lead transplant practitioners for current practice around polyvalent Ig use in post‐transplant recipients across Canada. Methods: We performed a survey study using short questionnaires to estimate rate of screening of HGG, use of polyvalent Ig, and physician's opinion on Ig treatment and infection prevention. Directors of 24 SOT and 23 HCT centers across Canada were invited to participate in the survey via an electronic mail. Results: Overall response rate was 63.8%. Twenty percent of SOT programs routinely measured Ig levels pre‐transplant compared to 33% of allogeneic (allo‐) and 21% of autologous (auto‐) HCT programs. Post‐transplant Ig levels were measured in 13%, 75%, and 29% in SOT, allo‐HCT, and auto‐HCT, respectively. The SOT and auto‐HCT groups indicated that they do not prescribe Ig therapy (100% and 86%), contrary to the allo‐HCT group (42%). Of the respondents in the SOT, allo‐HCT, and auto‐HCT groups, 60%, 67%, and 36%, respectively, thought infections could be prevented with intravenous immunoglobulins (IVIg). A majority of respondents indicated they would be interested in participating in a randomized controlled trial evaluating the use of IVIg in the SOT and in both HCT groups (100%, 83%, and 57%, respectively). Conclusions: Our study shows significant variation in practice between SOT and HCT centers with respect to screening and management of HGG. There is willingness to participate in a randomized controlled trial to address whether Ig treatment reduces infection in post‐transplant recipients.